Barriers in reaching new-borns and infants through home visits: A qualitative study using nexus planning framework - Deshmukh, Vaishali; John, Shibu; Pakhare, Abhijit; Dasgupta, Rajib; Joshi, Ankur; Chaturvedi, Sanjay; Goswami, Kiran; Das, Manoja Kumar; Mukhopadhyay, Rupak; Singh, Rakesh; Shrivastava, Pradeep; Dhingra, Bhavna; et al. (Frontiers in Public Health, 2022)
Background Home visitation has emerged as an effective model to provide high-quality care during pregnancy, childbirth, and post-natal period and improve the health outcomes of mother- new born dyad. This 3600 assessment documented the constraints faced by the community health workers (known as the Accredited Social Health Activists, ASHAs) to accomplish home visitation and deliver quality services in a poor-performing district and co-created the strategies to overcome these using a nexus planning approach. Methods The study was conducted in the Raisen district of Madhya Pradesh, India. The grounded theory approach was applied for data collection and analysis using in-depth interviews, and focus group discussions with stakeholders representing from health system (including the ASHAs) and the community (rural population). A key group of diverse stakeholders were convened to utilize the nexus planning five domain framework (social-cultural, educational, organizational, economic, and physical) to prioritize the challenges and co-create solutions for improving the home visitation program performance and quality. The nexus framework provides a systemic lens for evaluating the success of the ASHAs home visitation program. Results The societal (caste and economic discrimination), and personal (domestic responsibilities and cultural constraints of working in the village milieu) issues emerged as the key constraints for completing home visits. The programmatic gaps in imparting technical knowledge and skills, mentoring system, communication abilities, and unsatisfactory remuneration system were the other barriers to the credibility of the services. The nexus planning framework emphasized that each of the above factors/domains is intertwined and affects or depends on each other for home-based maternal and newborn care services delivered with quality through the ASHAs. Conclusion The home visitation program services, quality and impact can be enhanced by addressing the social-cultural, organizational, educational, economic, and physical nexus domains with concurrent efforts for skill and confidence enhancement of the ASHAs and their credibility.